2014
DOI: 10.1016/j.amjmed.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Caffeine Intake and Risk of Incident Tinnitus

Abstract: Background Caffeine is a commonly consumed substance that has long been thought to play a role in the development of tinnitus, but prospective data are lacking. We prospectively evaluated the association between caffeine intake and self-reported tinnitus in a female cohort. Methods Participants were 65,085 women in the Nurses Health Study II, aged 30–44 years and without tinnitus at baseline in 1991, who completed questionnaires about lifestyle and medical history every two years and food frequency questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…Knowledge on the burden of tinnitus in the general adult population comes from a few large prospective studies, mostly from northern Europe and the United States, providing data on tinnitus incidence [5,6,7]. To our knowledge, only 20 previous studies from 14 countries reported information on adult tinnitus prevalence using surveys recorded at a national or sub-national level.…”
Section: Introductionmentioning
confidence: 94%
“…Knowledge on the burden of tinnitus in the general adult population comes from a few large prospective studies, mostly from northern Europe and the United States, providing data on tinnitus incidence [5,6,7]. To our knowledge, only 20 previous studies from 14 countries reported information on adult tinnitus prevalence using surveys recorded at a national or sub-national level.…”
Section: Introductionmentioning
confidence: 94%
“…However, the role of the sex difference on tinnitus loudness and annoyance is still inconclusive (14,15). Also, higher caffeine intake may reduce the risk of tinnitus in women (5). On the contrary, the acute effects of caffeine withdrawal may add to the burden associated with tinnitus (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, age, gender, hearing loss and tinnitus duration were associated with tinnitus-related loudness and/or distress (3,4). Increased caffeine intake has been demonstrated to be associated with a lower risk of tinnitus in women (5).…”
mentioning
confidence: 99%
“…In three observational studies, higher caffeine intake was associated with a lower prevalence of tinnitus. 10,34,35 Of course, a causal relationship for a protective effect of caffeine against neuro-otological problems cannot be deduced from these observations.…”
Section: Caffeine Restrictionmentioning
confidence: 99%